2016
DOI: 10.1159/000450619
|View full text |Cite
|
Sign up to set email alerts
|

Uremic Toxin-Producing Gut Microbiota in Rats with Chronic Kidney Disease

Abstract: Background: In patients with chronic kidney disease (CKD), many metabolites of gut microbiota retain in the body as uremic toxins (UTs). However, the kinds of bacteria producing UTs are rarely discussed. Methods: We analyzed UT production and the composition of gut microbiota in CKD rats and cecectomized rats. AST-120, a spherical carbon adsorbent, was administrated to evaluate how the precursors of UT affect gut microbiota. Serum and urine levels of UTs were quantified by liquid chromatography/electrospray io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 30 publications
6
57
1
Order By: Relevance
“…Many more colonderived solutes have been identified in rats and mice in which suppression of microbial solute production is easier to accomplish. Studies in these species have identified at least 27 colon-derived solutes which are normally excreted in the urine and/or accumulate in the plasma when kidney function is reduced (Supplemental Table 5) (1,(22)(23)(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Many more colonderived solutes have been identified in rats and mice in which suppression of microbial solute production is easier to accomplish. Studies in these species have identified at least 27 colon-derived solutes which are normally excreted in the urine and/or accumulate in the plasma when kidney function is reduced (Supplemental Table 5) (1,(22)(23)(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota manipulates the processes leading to CKD through inflammatory [25], endocrine [20], and neurologic pathways [90]; a healthy gut microbiota protects the CKD, whereas gut dysbiosis contributes to the development of CKD [2]. In fact, CKD is associated with alterations in the gut microbiota; species producing uremic toxins, such as Enterobacteriaceae, Clostridiaceae, Pseudomonadaceae, and Bacteroidiaceae, are increased, whereas beneficial species, such as Lactobacillaceae, Bifidobacteriaceae, and Prevotellaceae, are decreased [101][102][103][104]. Consistently, fecal transplantation from CKD patients to antibiotic-treated mice results in an increase in the plasma TMAO levels [29].…”
Section: Gut-kidney Crosstalk and Inflammation In The Development Of Ckdmentioning
confidence: 99%
“…Testing the isolated effect of the loss of kidney function on microbiome composition is only possible in experimental models. In several studies exploring the effects of surgically induced CKD in rats, total richness was reduced in CKD and the microbial community was differentially structured [6,8]. Andersen et al performed a similar analysis in collagen type IV α3-deficient mice with Alport syndrome-related progressive CKD.…”
Section: Gut Microbiota In Ckdmentioning
confidence: 99%